The pattern of development for gene expression of sterol regulatory element binding transcription factor 1 in pigs - J. Jiang; Z. XU; X. Han; F. Wang; L. Wang (Czech Journal of Animal Science, 2006)
Sterol regulatory element-binding transcription factor 1 (SREBF1) has been implicated as a key regulator of adipocyte differentiation and lipid metabolism. The pattern of SREBF1 gene expression in different growth stages and the relation with adipose deposition is studied. Fifteen female Duroc × Landrace × Yorkshire pigs in five groups, each group of three pigs at live weight 1, 30, 50, 70 and 90 kg, were used to study the developmental gene expression of SREBF1 in the subcutaneous adipose tissue by means of semi-quantitative RT-PCR. The results showed that porcine SREBF1 mRNA was present in a very low concentration at birth and continually increased to the highest expression at 90 kg growth stages, SREBF1 mRNA levels increased as pigs grew and deposited fat from 1 to 90 kg live weights (P < 0.05). The present data indicated a close positive correlation between the levels of SREBF1 gene expression and the fat deposition rate in pigs (P < 0.05).